Tinjauan Yuridis Terhadap Peran Polisi Lalu Lintas Dalam Pelaksanaan Alternative Dispute Resolution (ADR) Terhadap Penyelesaian Kasus Kecelakaan Di Wilayah Kabupaten Kutai Kartanegara - Aji Titin Roswitha Nursanthy; Maria Ana Liwa; Sunarto (Collegium Studiosum Journal, 2021)
The implementation of ADR (Alternative Dispute Resolution) on the settlement of accident cases in the Kutai Kartanegara Regency area is the main step for the Kutai Kartanegara Traffic Police to handle the accident case. Therefore, in this study will further study the role of Kutai Kartanegara Traffic Police to the implementation of ADR (Alternative Dispute Resolution) and solve accident cases. This research is an empirical juridical law study. Through a sociological juridical research approach. The research location is located in the Police Satlantas Kutai Kartanegara Regency, types and sources using primary data and secondary data, techniques obtained data obtained through primary data collection techniques by interview while secondary data collection techniques obtained from literature studies.